FGF21 decreases food intake and body weight in obese Göttingen minipigs. Issue 3 (20th November 2018) - Christoffersen, Berit; Straarup, Ellen M.; Lykkegaard, Kirsten; Fels, Johannes J.; Sass‐Ørum, Kristian; Zhang, Xujia; Raun, Kirsten; Andersen, Birgitte
Abstract : Aims: The aim of this study was to assess the effect of FGF21 on food intake, body weight, body composition, glucose homeostasis, bone mineral density (BMD), cortisol and growth hormone (GH) in obese minipigs. The pig is a unique model for studying FGF21 pharmacology as it does not express UCP1, unlike mice and humans. Methods: Twelve obese Göttingen minipigs with a mean body weight of 91.6 ± 6.7 kg (mean ± SD) received subcutaneously either vehicle (n = 6) or recombinant human FGF21 (n = 6) once daily for 14 weeks (0.1 mg/kg for 9.5 weeks and 0.3 mg/kg for 4.5 weeks). Results: Treatment of obese minipigs with FGF21 led to a 50% reduction in food intake and a body weight loss of, on average, 18 kg compared to the vehicle group after 14 weeks of dosing. Glucose tolerance and insulin sensitivity, evaluated by intravenous glucose tolerance test, were significantly improved in the FGF21 group compared to the vehicle group at the end of the study. The plasma cortisol profile was unaffected by FGF21, whereas a small decrease in peak GH values was observed in the FGF21‐treated animals after 7 to 9.5 weeks of treatment compared to the vehicle group. Whole‐body BMD was not affected by 13 weeks of FGF21 dosing. Conclusion: Despite a lack of UCP‐1 in obese minipigs, FGF21 treatment induced a significant weight loss, primarily a result of reduction in food intake, with no adverse effect on BMD or plasma cortisol.